Modelado de la isoterma de adsorción de zanahorias deshidratadas - Anria, Marialina; González, Astrid; Quintero, Rosa (Universidad Tecnológica de Panamá, 2019)
The behavior of the adsorption isotherms is important since these guarantee the stability of the food products during the drying,packaging and storage processes. In this study, the carrot sorption isotherm was determined at a temperature of 22ºC ± 1 ° C applying the methodof static gravimetry method in a range of water activity (Aw) between 0.113 and 0.883. The data were adjusted using the GAB, BET and Hendersonmathematical models and the quality of the adjustment was evaluated with the regression coefficient (R2). An isotherm type II was obtained, whichis typical for fruits and vegetables. The humidity of the monolayer (Wo) was slightly lower in the BET model than in that of GAB, with values of0.102 and 0.125 g water / g of m.s, respectively, which agrees with the literature consulted. All models presented an adjustment higher than 0.92.However, those that best adjusted to the behavior of the experimental data were BET and GAB, which presented an R2 of 0.975 and 0.994,respectively.
Modelling of moisture sorption isotherms of dehydrated carrot
El comportamiento de las isotermas de adsorción es importante ya que estos garantizan la estabilidad de los productosalimenticios durante los procesos de secado, envasado y almacenamiento. En este estudio se determinó a una temperatura de 22ºC ±1°C la isotermade sorción de zanahoria aplicando el método de gravimetría estática en un rango de actividad de agua (Aw) entre 0.113 y 0.883. Los datos seajustaron utilizando los modelos matemáticos GAB, BET y Henderson y la calidad del ajuste se evaluó con el coeficiente de regresión (R2). Seobtuvo una isoterma tipo II, la cual es típica para frutas y vegetales. La humedad de la monocapa (Wo) fue ligeramente menor en el modelo de BETque en el de GAB, con valores de 0.102 y 0.125 g agua/g de m.s., respectivamente, lo cual concuerda con la literatura consultada. Todos los modelospresentaron un ajuste superior a 0.92. Sin embargo, los que mejor se ajustaron al comportamiento de los datos experimentales fue de BET y GAB,los cuales presentaron un R2 de 0.975 y 0.994, respectivamente.